IMPROVE-BMT: a protocol for a pilot randomised controlled trial of prehabilitation exercise for adult haematopoietic stem cell transplant recipients. Issue 1 (18th January 2023) - Potiaumpai, Melanie; Schmitz, Kathryn H; Mineishi, Shin; Naik, Seema; Wirk, Baldeep; Rakszawski, Kevin; Ehmann, W Christopher; Claxton, David; Nickolich, Myles; Zemel, Babette S; Zheng, Hong
Abstract : Introduction: Haematopoietic stem cell transplant (HSCT) in adults is an intensive medical procedure for a variety of haematological malignancies. Although there is a large body of evidence demonstrating the negative effects of HSCT on physical function and psychosocial parameters, there is limited evidence on the impact of HSCT on body composition and bone health. Further, aerobic and resistance-training exercise interventions aimed at improving physical function and patient-reported outcomes largely take place during the peritransplant and post-transplant period. Prehabilitative exercise, or exercise prior to medical treatment, has been successfully deployed in presurgical candidates and other tumour sites, yet there is a paucity of evidence on the effect of prehabilitation in HSCT patients. The aim of this study is to investigate the feasibility, acceptability and safety of a resistance training exercise programme in patients with haematological malignancies prior to HSCT. Methods and analysis: IMpact of PRehabilitation in Oncology Via Exercise-Bone Marrow Transplant is a single-site, pilot randomised controlled trial of an exercise intervention compared with usual care. The primary aim is to assess the feasibility, acceptability and safety of the resistance-training exercise intervention prior to HSCT. Secondary aims include evaluating the differences in physical function, body composition, bone mineral density and patient-reported outcomes between the exercise group and usual care control group. Outcome measurements will be assessed: prior to HSCT, on/around day of HSCT admission, +30 days post-HSCT and +100 days post-HSCT. The exercise intervention is a home-based resistance training exercise programme that incorporates resistance band and body weight exercises. The primary outcomes will be reported as percentages and/or mean values. The secondary outcomes will be analysed using appropriate statistical methods to portray within-group and between-group differences. Ethics and dissemination: The study has Penn State College of Medicine approval. Results will be disseminated through scientific publication and presentation at exercise-related and oncology-related scientific meetings. Trial registration number: NCT03886909 .